Clinical Skills Abilities Development During COVID-19 Pandemic in Mexico City - Lourdes Adriana Medina-Gaona (University Library System, University of Pittsburgh, 2020)
Medical formation includes the development of several skills including clinical ones. Medical students have to learn how to build a healthy doctor - patient relationship in order to provide the best diagnosis, treatment and quality of attention. COVID-19 provide a new challenge for all students in Mexico to learn skills that traditionally have been learned in person and not through a computer.